Impact of gender, urbanization, and food preference on university students' body composition post-COVID-19 - Sanjeev Kumar; Hemantajit Gogoi; Somanpreet Singh; Mukesh Kumar Verma; Kuldeep Nara; Swati Choudhary; Parveen Kumar; Poli Borah; Karuppasamy Govindasamy (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: The COVID-19 lockdown significantly altered university students' lifestyles, affecting their physical activity and dietary habits, which impacted their body composition.